Chiral acyl radicals generated by visible light enable stereoselective access to 3,3-disubstituted oxindoles: application toward the synthesis of (–)- and (+)-physovenine - Späth, Josef (Department of Chemistry, 2025)
Radical species serve as powerful tools for carbon-carbon bond formation in synthetic organic chemistry. Such species can be formed in an efficient and environmentally friendly manner by way of photoredox catalysis, which uses a photocatalyst in conjunction with visible light (typically) to generate the necessary environment for radical generation under extremely mild conditions. This work outlines the development of a novel imidazolidinone-derived acyl radical, generated under photoredox catalysis, and its application toward the stereoselective synthesis of 3,3- disubstituted oxindoles via an additional-cyclisation cascade sequence to acrylamide precursors. 6 oxindoles were produced in up to 85% yield, with moderate diastereoselectivity of up to 2.2:1, but which could be easily separated by standard chromatography to yield pure diastereomers. Mechanistic studies, by virtue of TEMPO-trapping experiments provided strong support for the existence of the proposed acyl-radical, and further synthetic utility of the research was demonstrated in formal synthesis of the natural product (–)-physovenine, a member of the biologically active cyclotryptamine alkaloids.